The New Da’wah Strategy among Millennial Generations through Tiktok During Pandemic - Fany Nur Rahmadiana Hakim; Ihsan Kamaludin; Shifa Nisrina Sujana (Islam Realitas: Journal of Islamic and Social Studies, 2021)
This research focuses on the strategy of public figures who develop religious content in order to spread religious values among the millennial generation, especially during the pandemic.  The rampant use of the TikTok platform during the COVID-19 pandemic was not only deployed as an entertainment medium but was also used by many people to be able to spread propaganda and missions to disseminate religious values among the millennial generation. This is due to the popularity of that platform has skyrocketed, making some content creators and public figures develop the marketing of their ideological values on social media. By using the theory of social change and the concept of the development of communication, the authors try to analyze the phenomena that in question. This study uses a qualitative descriptive method with the TikTok application observation technique and seeks to explore various information in depth to find various facts that can explain this phenomenon. We also found that millennials who use the TikTok platform often start to look at various religious content and some are even active in filling the content because they are inspired by public figures who spread similar content. Moreover, some lecturers often provide religious information using music or duet features so as to encourage application users to spread religious teachings and share religious knowledge.Penelitian ini berfokus pada strategi tokoh masyarakat yang mengembangkan konten religi dalam rangka menyebarkan nilai-nilai agama di kalangan generasi milenial, terutama di masa pandemi. Maraknya penggunaan platform TikTok di masa pandemi COVID-19 tidak hanya dijadikan sebagai media hiburan tetapi juga dimanfaatkan oleh banyak orang untuk bisa menyebarkan dakwah dan misi penyebarluasan nilai-nilai agama di kalangan generasi milenial. Hal ini dikarenakan popularitas platform tersebut yang meroket, membuat beberapa content creator dan public figure mengembangkan pemasaran nilai-nilai ideologisnya di media sosial. Dengan menggunakan teori perubahan sosial dan konsep perkembangan komunikasi, peneliti mencoba menganalisis fenomena yang terjadi. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik observasi aplikasi TikTok dan berupaya menggali berbagai informasi secara mendalam sehingga mampu menemukan berbagai fakta yang dapat menjelaskan fenomena tersebut. Kami juga menemukan bahwa generasi milenial yang menggunakan platform TikTok sering mulai melihat berbagai konten religi dan bahkan ada yang aktif mengisi konten tersebut karena terinspirasi oleh tokoh masyarakat yang menyebarkan konten serupa. Apalagi beberapa dosen sering memberikan informasi agama dengan menggunakan fitur musik atau duet sehingga mendorong pengguna aplikasi untuk dapat menjalankan ajaran agama dan membagikan ilmu agama